2008
DOI: 10.1177/0022466907313605
|View full text |Cite
|
Sign up to set email alerts
|

Schooling and the Construction of Identity Among Minority Students in Spain and the United States

Abstract: Based on a study of the special education placement process in a large city in the United States and two studies in different regions of Spain, the authors offer a comparative analysis of the relationship between professional beliefs and practices and the achievement of culturally and linguistically diverse (CLD) students. The data focus on African American and Hispanic students in the United States and on Gitano (Gypsy) and Moroccan students in Spain. Although professional attitudes in both countries revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
1
27
1
13
Order By: Relevance
“…Further, the positive effect of school inclusion on GPA remained significant over a 3‐year period, and inclusion accounted for substantial variance in the model that did not diminish over time. These longitudinal findings with a diverse sample expand upon previous studies showing students with disabilities in schools that are inclusive do better academically (Harrower, 1999; Katz & Mirinda, 2002; Salend & Garrick Duhaney, 1999) and qualitative studies demonstrating teacher beliefs and behaviors are linked with academic achievement of students of color (Harry, Arnaiz, Klingner, & Sturges, 2008; Murray & Naranjo, 2008). Thus, when schools work to implement inclusive best practices, there is a lasting positive effect on the grades of students.…”
Section: Discussionsupporting
confidence: 73%
“…Further, the positive effect of school inclusion on GPA remained significant over a 3‐year period, and inclusion accounted for substantial variance in the model that did not diminish over time. These longitudinal findings with a diverse sample expand upon previous studies showing students with disabilities in schools that are inclusive do better academically (Harrower, 1999; Katz & Mirinda, 2002; Salend & Garrick Duhaney, 1999) and qualitative studies demonstrating teacher beliefs and behaviors are linked with academic achievement of students of color (Harry, Arnaiz, Klingner, & Sturges, 2008; Murray & Naranjo, 2008). Thus, when schools work to implement inclusive best practices, there is a lasting positive effect on the grades of students.…”
Section: Discussionsupporting
confidence: 73%
“…An important finding from our review is that ethnic minority children are often rated as having more ADHD symptoms than nonminority children, yet less often diagnosed and medically treated. One possible explanation is that cultural, racial, and language biases may be leading to the overidentification of ethnic minority children as disabled, who are, in turn, disproportionately overrepresented in special education (e.g., Artiles, 2003;Harry, Arnaiz, Klingner, & Sturges, 2008). In her ethnographic study of 48 mothers of children with psychiatric disorders (primarily ADHD and autism), Blum (2011Blum ( , 2015 revealed how the diagnosis of these disorders intersects with social class, race, and gender, resulting in overdiagnosis in children of color.…”
Section: Discussionmentioning
confidence: 99%
“…Scarborough et al (2004) reported that 50% of African American children receiving EI services lived in poverty or were born at low birth weight—factors that themselves increase the risk of delays or disabilities (e.g., Hogan & Park, 2000) and so should make participation in EI/ECSE more likely. Cultural, linguistic, and racial bias, which may cause minority children’s abilities and behaviors to be considered relatively more problematic, is a second possible mechanism (Coutinho & Oswald, 2000; Harry, Arnaiz, Klingner, & Sturges, 2008; Hays, Prosek, & McLeod, 2010). For instance, teachers have sometimes been reported to be more likely to refer children who are minorities for special education (e.g., Hosp & Reschley, 2003).…”
Section: Are Minority Children Disproportionately Represented In Ei/ecse?mentioning
confidence: 99%